Controls data flow in distributed computing systems - Іванкевич, О. В.; Лукашенко, В. В. (Problems of Informatization and Management, 2010)
This work is dedicated to creation of dataflow control system within a distributed calculation computer network system on the basis of expert system. The existing mechanisms of receiving, storing and processing of large amount of data in distributed systems and the peculiarities of effectiveness improve of computer networks are researched. The means of intelligent control over the dataflow using distributed calculation systems are proposed